Zabytkowe dzwony kościelne na terenie diecezji kieleckiej. Warsztaty i twórcy - Karkocha, Małgorzata (Przegląd Nauk Historycznych, 2015)
On the basis of available literature, materials collected in the Archives of the Diocese of Kielce, the Regional Office for the Protection of Monuments in Kielce and Krakow, as well as a result of field research conducted partly by the Author it can be concluded, that in the Diocese of Kielce there have been preserved, i.e. saved from requisitions and destruction of war, about 120 historic church bells. All of them date back to the period before 1900. Only 41 of those (fewer than half) bear a name and a surname of the bell-founder and a name of the location of the workshop. Bells cast in the 14th and 15th century, usually inscribed with the Latin words „O rex gloriae veni cum pace”, remain completely anonymous to us. Only one signed bell from the 16th century is still extant in Zagość. There have also been preserved two bells dating back to the next century, both produced for the church in Małogoszcz by Benedict Briot from Lorraine, who worked in Poland. The largest number of signed specimens (as many as 33) come from the 18th century. Among them there prevail bells from two famous bell foundries located in Gdańsk, namely the ones produced by the Wittwerck and Anthony families, and those coming from an equally active Kraków workshops belonging to the Weidner family, to Ignatius Huflauer and to Balthazar Ruszkowski (vel Roszkiewicz, Rośkiewicz). Only a few bells found in the 19th century bear a signature of the producer. The majority of them were smelt from older, damaged specimens and were manufactured by bell founders located in Warsaw (M. Petersilge, M.A. Zwoliński) or in Kraków (A. Fortuński).